Squamous cell carcinoma antigen 1 is associated to poor prognosis in esophageal cancer through immune surveillance impairment and reduced chemosensitivity. Issue 5 (15th April 2019) - Turato, Cristian; Scarpa, Melania; Kotsafti, Andromachi; Cappon, Andrea; Quarta, Santina; Biasiolo, Alessandra; Cavallin, Francesco; Trevellin, Elisabetta; Guzzardo, Vincenza; Fassan, Matteo; Chiarion‐Sileni, Vanna; Castoro, Carlo; et al.
Abstract : Squamous cell carcinoma antigen‐1 (SCCA1) overexpression is associated with poor prognosis and chemoresistance in several tumor types, however, the underlying mechanisms remain elusive. Here, we report SCCA1 in relation to the immune and peritumoral adipose tissue microenvironment in early and advanced esophageal adenocarcinoma (EAC). In our series of patients with EAC, free SCCA1 serum levels were associated with significantly worse overall survival, and SCCA1‐IgM serum levels showed a trend to a worse overall survival. Serum SCCA1 and intratumoral SCCA1 were inversely correlated with immune activation markers. In agreement with these findings, SCCA1 induced the expression of the immune checkpoint molecule programmed death ligand‐1 on monocytes and a direct correlation of these 2 molecules was observed in sequential tumor sections. Furthermore, SCCA1 mRNA expression within the tumor was inversely correlated with stem cell marker expression both within the tumor and in the peritumoral adipose tissue. In vitro, in EAC cell lines treated with different chemotherapeutic drugs, cell viability was significantly modified by SCCA1 presence, as cells overexpressing SCCA1 were significantly more resistant to cell death. In conclusion, poor prognosis in EAC overexpressing SCCA1 is due to reduced tumor chemosensitivity as well as intratumoral immunity impairment, likely induced by this molecule. Abstract : This study explores squamous cell carcinoma antigen‐1 (SCCA1) in relation to the immune and peritumoral adipose tissue microenvironment in early and advanced esophageal adenocarcinoma. The authors found that poor prognosis in EAC overexpressing SCCA1 is due to reduced tumor chemosensitivity as well as intratumoral immunity impairment, likely induced by this molecule.